Vector competence of Culex mosquitoes (Diptera: Culicidae) in Zika virus transmission: an integrative review - Sandro G. Viveiros-Rosa; Eduardo G. Regis; Wilson C. Santos (Pan American Health Organization, 2020)
Objective. To identify studies on the competence of Culex mosquitoes as vectors for the transmission of Zika virus (ZIKV) around the globe. Methods. We performed an integrative review to identify relevant articles on specific experiments to determine whether Culex mosquitoes are vectors for ZIKV. The sources we used for our research were the Brazilian Periódicos CAPES electronic portal (MEDLINE/PubMed, ScienceDirect Journals, Nature Publishing Group, SciELO, Springer Link, and 250 other databases) and gray literature. Results. We identified 344 studies, of which 36 were considered for this review. In 8 studies, infection in salivary glands of Culex quinquefasciatus, Culex restuans, Culex tarsalis, and Culex coronator was detected. Cx. quinquefasciatus was the most studied among those confirmed as potential ZIKV vectors, and only strains of Asian lineages (THA/2014/SV0127-14; SZ01 (2016)) and American lineages (BRPE243 (2015); PRVABC59 (2015)) can infect the salivary glands of Culex mosquitoes. The tested African strains (MR766 and DAK AR 41525) were unable to infect salivary glands. Conclusions. There is still a lack of compelling evidence that indicates Culex spp. are a competent ZIKV vector, but they should remain a target for further monitoring studies, especially regarding ZIKV transmission to other species. Furthermore, studies should not be limited to studying whether their salivary glands are infected.